2017
DOI: 10.18632/oncotarget.21814
|View full text |Cite
|
Sign up to set email alerts
|

Ataxin-1 is involved in tumorigenesis of cervical cancer cells via the EGFR-RAS–MAPK signaling pathway

Abstract: Ataxin-1 (ATXN1) is a coregulator protein within which expansion of the polyglutamine tract causes spinocerebellar ataxia type 1, an autosomal dominant neurodegenerative disorder. Previously, we reported that ATXN1 regulates the epithelial–mesenchymal transition of cervical cancer cells. In the present study, we demonstrate that ATXN1 is involved in cervical cancer tumorigenesis by promoting the proliferation of human cervical cancer cells. Chromatin immunoprecipitation assays showed that ATXN1 bound to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…4 F ). A link between ataxin-1 and cell proliferation has been recently described, and mitogen-activated protein kinase (MAPK) signaling was shown to be critical in mediating this function ( 22 ). The “regulation of MAPK cascade” term was found enriched also in our GO analysis, supporting its possible involvement in B cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…4 F ). A link between ataxin-1 and cell proliferation has been recently described, and mitogen-activated protein kinase (MAPK) signaling was shown to be critical in mediating this function ( 22 ). The “regulation of MAPK cascade” term was found enriched also in our GO analysis, supporting its possible involvement in B cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, ATXN1 is a component of the Notch signaling pathway [ 22 ], and the Notch signaling reportedly mediates tumor cell migration and invasion induced by low oxygen supply (hypoxia), which is a critical characteristic of solid tumors [ 23 ]. Previous studies have demonstrated that a potential link between ATXN1 expression (both upregulation and downregulation) and cancer development in humans could regulate cell proliferation and the epithelial-mesenchymal transition of cells in various cancers [ 24 , 25 ], but it remains unknown whether ATXN1 acts as a tumor suppressor or an oncogene. Therefore, the ATXN1 might play an important role in the OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to highlighting known cancer genes, uKIN also ranks highly several non-CGC genes that may or may not play a functional role in cancer, as our knowledge of cancer-related genes is incomplete. Among these novel predictions for GBM are ATXN1, SMURF1, and CCR3, all of which have been recently suggested to play a role in cancers [45][46][47] and are each mutated in less than 5% of the samples. ATXN1 is a chromatin-binding factor that plays a critical role in the development of spinocerebellar ataxia, a neurodegenerative disorder [48], and mutants of ATXN1 have been found to stimulate the proliferation of cerebellar stem cells in mice [49].…”
Section: Resultsmentioning
confidence: 99%